2013
DOI: 10.1614/ws-d-12-00178.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Formulation and Application Time of Day on Detecting Dicamba in the Air under Field Conditions

Abstract: The development of dicamba-tolerant and other auxin-tolerant crops will enable the use of these effective herbicides in soybean and cotton at application timings such as at planting or over-the-top that are not currently possible. This research examined the effect of various factors on detection of postapplication amounts of dicamba in the air under field conditions by coupling a sample collection system with advanced chemical analysis of those samples. The quantity of dimethylamine salt of dicamba that was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 26 publications
5
77
1
2
Order By: Relevance
“…This research was conducted in the fall of 2017 and used methods from previous research by Mueller et al (2013) and Gavlick et al (2016). Expendable supplies included plastic trays to hold the sprayed material, clear plastic vented humidity domes, soil, and the aforementioned sampling media.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This research was conducted in the fall of 2017 and used methods from previous research by Mueller et al (2013) and Gavlick et al (2016). Expendable supplies included plastic trays to hold the sprayed material, clear plastic vented humidity domes, soil, and the aforementioned sampling media.…”
Section: Methodsmentioning
confidence: 99%
“…This research utilized air samplers previously demonstrated to be effective in collecting dicamba from the atmosphere (Mueller et al 2013). The air sampler and associated sample collection hardware are available from Hi-Q Environmental Products Co. (San Diego, CA, USA; https://www.hi-q.net/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vapor drift, conversely, is primarily a function of volatilization that takes place after spray particles reach their intended site. This form of drift can be influenced by various abiotic factors, such as temperature and relative humidity [4,5]. Increased temperature and low humidity tend to intensify the risk for volatility to occur by increasing the amount of atmospheric space for evaporation to take place [4].…”
Section: Introductionmentioning
confidence: 99%
“…This form of drift can be influenced by various abiotic factors, such as temperature and relative humidity [4,5]. Increased temperature and low humidity tend to intensify the risk for volatility to occur by increasing the amount of atmospheric space for evaporation to take place [4]. Auxin-type herbicide residues, such as 2,4-D and dicamba, are known to be difficult to clean from spray equipment, and small amounts of these compounds could be inadvertently applied to susceptible crops if the same equipment was subsequently used to treat non-dicamba or non-2,4-D-resistant crops [6].…”
Section: Introductionmentioning
confidence: 99%